An adverse outcome pathway for small intestinal tumors in mice involving chronic cytotoxicity and regenerative hyperplasia: a case study with hexavalent chromium, captan, and folpet. (13th September 2020) - Bhat, Virunya S.; Cohen, Samuel M.; Gordon, Elliot B.; Wood, Charles E.; Cullen, John M.; Harris, Mark A.; Proctor, Deborah M.; Thompson, Chad M.
Abstract: Small intestinal (SI) tumors are relatively uncommon outcomes in rodent cancer bioassays, and limited information regarding chemical-induced SI tumorigenesis has been reported in the published literature. Herein, we propose a cytotoxicity-mediated adverse outcome pathway (AOP) for SI tumors by leveraging extensive target species- and site-specific molecular, cellular, and histological mode of action (MOA) research for three reference chemicals, the fungicides captan and folpet and the transition metal hexavalent chromium (Cr(VI)). The gut barrier functions through highly efficient homeostatic regulation of SI epithelial cell sloughing, regenerative proliferation, and repair, which involves the replacement of up to 10 11 cells per day. This dynamic turnover in the SI provides a unique local environment for a cytotoxicity mediated AOP/MOA. Upon entering the duodenum, cytotoxicity to the villous epithelium is the molecular initiating event, as indicated by crypt elongation, villous atrophy/blunting, and other morphologic changes. Over time, the regenerative capacity of the gut epithelium to compensate declines as epithelial loss accelerates, especially at higher exposures. The first key event (KE), sustained regenerative crypt proliferation/hyperplasia, requires sufficient durations, likely exceeding 6 or 12 months, due to extensive repair capacity, to create more opportunities for the second KE, spontaneous mutation/transformation, ultimately leading to proximal SI tumors. Per OECD guidance, biological plausibility, essentiality, and empirical support were assessed using modified Bradford Hill considerations. The weight-of-evidence also included a lack of induced mutations in the duodenum after up to 90 days of Cr(VI) or captan exposure. The extensive evidence for this AOP, along with the knowledge that human exposures are orders of magnitude below those associated with KEs in this AOP, supports its use for regulatory applications, including hazard identification and risk assessment.